A new species of Pharaxonotha Reitter (Coleoptera: Erotylidae) from central South America - Skelley, Paul E.; Segalla, Rosane (Zootaxa, 2019)
Pharaxonotha cerradensis, new species (Coleoptera: Erotylidae), is described from Bolivia and Brazil. It belongs in a complex of species from Mexico and Central America that radiated on host cycads of the genus Zamia L. (Cycadales: Zamiaceae) and is associated with Zamia boliviana (Brongniart) A. DC. (Cycadales: Zamiaceae). Pharaxonotha cerradensis is compared with other species of Pharaxonotha Reitter.